ECONOMIC THEORY: CRITICAL NOTES AND ADDITIONS TO SOME CATEGORIES - A. Urunov (Вестник университета)
In article it is proved and specified fundamental categories of the economic theory such as «economy», «market» and «the pricing mechanism» a misinterpretation of which conducts to the reader's delusion. The main arguments and the author's arguments in contents of these terms taking into account new realities in market economy are adduced.